Studies of nucleon resonance structure in exclusive meson electroproduction - Aznauryan, I. G.; Bashir, A.; Braun, V. M.; Brodsky, S. J.; Burkert, V. D.; Chang, L.; Chen, Ch; El-Bennich, B. [UNESP]; Cloët, I. C.; Cole, P. L.; Edwards, R. G.; Fedotov, G. V.; et al. (World Scientific Publishing, 2013)
Studies of the structure of excited baryons are key factors to the N* program at Jefferson Lab (JLab). Within the first year of data taking with the Hall B CLAS12 detector following the 12 GeV upgrade, a dedicated experiment will aim to extract the N* electrocouplings at high photon virtualities Q 2. This experiment will allow exploration of the structure of N* resonances at the highest photon virtualities ever achieved, with a kinematic reach up to Q2 = 12 GeV2. This high-Q 2 reach will make it possible to probe the excited nucleon structures at distance scales ranging from where effective degrees of freedom, such as constituent quarks, are dominant through the transition to where nearly massless bare-quark degrees of freedom are relevant. In this document, we present a detailed description of the physics that can be addressed through N* structure studies in exclusive meson electroproduction. The discussion includes recent advances in reaction theory for extracting N* electrocouplings from meson electroproduction off protons, along with Quantum Chromodynamics (QCD)-based approaches to the theoretical interpretation of these fundamental quantities. This program will afford access to the dynamics of the nonperturbative strong interaction responsible for resonance formation, and will be crucial in understanding the nature of confinement and dynamical chiral symmetry breaking in baryons, and how excited nucleons emerge from QCD. © 2013 World Scientific Publishing Company.
Keywords: Baryon resonances; CLAS; Confinement; Dispersion relations; Dynamical chiral symmetry breaking; Electromagnetic form-factors; Jefferson lab; Lattice QCD calculations; Meson production; Nonperturbative QCD; Quark models